ASPEKTUALITAS DALAM NOVEL THE GREAT GATSBY OLEH F. SCOTT FITZGERALD - Eka Susylowati (Prasasti: Journal of Linguistics)
This research aims to reveal the form and marker of aspectuality in The Great Gatsby novel written by F. Scott Fitzgerald. The data in this study are written data in the form of words, clauses, and sentences in the novel The Great Gatsby. It was written by F. Scott Fitzgerald  consists of three forms of aspectuality namely perfective / completed, progressive, and repetitive / habitual. The aspect that is often used is perfective / completed aspiration. Aspectuality markers used including perfective aspect characterized by past verb or had + past participle verb, while progressive aspect are marked to be + verb ing, and repetitive / habitual are marked with past verb or infinitive forms.